Inhibition of Oxidative Phosphorylation Reverses Bone Marrow Hypoxia Visualized in Imageable Syngeneic B-ALL Mouse Model - Rytelewski, Mateusz; Harutyunyan, Karine; Baran, Natalia; Mallampati, Saradhi; Zal, M. Anna; Cavazos, Antonio; Butler, Jason M.; Konoplev, Sergej; El Khatib, Mirna; Plunkett, Shane; Marszalek, Joseph R.; Andreeff, Michael; et al. (Frontiers in Oncology, 2020)
Abnormally low level of interstitial oxygen, or hypoxia, is a hallmark of tumor microenvironment and a known promoter of cancer chemoresistance. Inside a solid tumor mass, the hypoxia stems largely from inadequate supply of oxygenated blood through sparse or misshapen tumor vasculature whilst oxygen utilization rates are low in typical tumor’s glycolytic metabolism. In acute leukemias, however, markers of intracellular hypoxia such as increased pimonidazole adduct staining and HIF-1α stabilization are observed in advanced leukemic bone marrows (BM) despite an increase in BM vasculogenesis. We utilized intravital fast scanning two-photon phosphorescence lifetime imaging microscopy (FaST-PLIM) in a BCR-ABL B-ALL mouse model to image the extracellular oxygen concentrations (pO2) in leukemic BM, and we related the extracellular oxygen levels to intracellular hypoxia, vascular markers and local leukemia burden. We observed a transient increase in BM pO2 in initial disease stages with intermediate leukemia BM burden, which correlated with an expansion of blood-carrying vascular network in the BM. Yet, we also observed increased formation of intracellular pimonidazole adducts in leukemic BM at the same time. This intermediate stage was followed by a significant decrease of extracellular pO2 and further increase of intracellular hypoxia as leukemia cellularity overwhelmed BM in disease end-stage. Remarkably, treatment of leukemic mice with IACS-010759, a pharmacological inhibitor of mitochondrial Complex I, substantially increased pO2 in the BM with advanced B-ALL, and it alleviated intracellular hypoxia reported by pimonidazole staining. High rates of oxygen consumption by B-ALL cells were confirmed by Seahorse assay including in ex vivo cells. Our results suggest that B-ALL expansion in BM is associated with intense oxidative phosphorylation (OxPhos) leading to the onset of metabolic BM hypoxia despite increased BM vascularization. Targeting mitochondrial respiration may be a novel approach to counteract BM hypoxia in B-ALL and, possibly, tumor hypoxia in other OxPhos-reliant malignancies.